Highly‐Sensitive and High Operating Range Fully‐Printed Humidity Sensors Based on BiFeO3/BiOCl Heterojunctions - Paul Fourmont; Fabrice Vaussenat; Mathieu Gratuze; Caroline A. Ross; Sylvain G. Cloutier (Advanced Electronic Materials)
Abstract Fully‐printed humidity sensors based on BiFeO3/BiOCl heterojunctions fabricated using a two‐step process with serigraphic printing are reported. Most importantly, this unique sensor architecture provides a broader relative humidity sensing range compared to pristine BFO sensors due to a synergistic effect between dense networks of BiOCl nanosheets synthetized atop BFO powders. With surface‐to‐weight ratios reaching 7.75 m2 g−1, these heterostructures increase the sensitivity and operating range of BFO‐based humidity sensors. While previously reported BFO humidity sensors only detect relative humidities above 30%, The BFO/BiOCl heterojunctions can measure relative humidities as low as 15% due to their increased surface area. Optimal growth and packing of the BiOCl nanosheet/BFO powder heterostructure are achieved by tuning the loading of the BFO powder and simultaneously forming the BiOCl sheets by chemical etching and annealing of the BFO powder. Excellent performance of optimized sensors including tracking and monitoring different types of breathing are demonstrated while mounted on an oxygen mask.